A Description Of Happiness In A Toba Batak Couple Who Doesn't Have Children - Cristina, Putri; Brahmana, Karina M (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
This study was conducted to understand and describe in depth how childless Toba Batak couples interpret and maintain happiness in their married lives. Through a qualitative approach using in-depth interviews with two married couples (Subject 1 and Subject 2), as well as further research through significant others (informants), it was found that happiness in marriage is not only determined by the presence of children as successors to the family, but is more determined by the quality of the relationship, the depth of communication, acceptance of reality, and the meaning of life that is built together in married life. From both couples who participated in this study, a strong similarity was found regarding the purpose of marriage. Although they do not have children, whether due to medical factors or because the process has not produced results, both still demonstrate determination and commitment to building a family that is spiritually prosperous. This is reflected in how they live their married life with love, emotional support, and healthy and open communication. They do not have children, whether due to medical factors or because the process has not produced results, both still demonstrate determination and commitment to building a family that is spiritually prosperous. This is reflected in how they live their married life with love, emotional support, and healthy and open communication. They do not interpret the absence of children as a failure in marriage, but rather as part of the dynamics of life that must be accepted and lived with maturity and sincerity.